Landasan Hukum Syar’i dan Hukum Positif Halal Haram Industri Produk Halal Indonesia - Efendi, Ahmad; Tawwab, M. Abdut; Siradjuddin, Siradjuddin; Arifin, Asriadi (Journal of Islamic Economic and Law (JIEL), 2024)
This paper will discuss Islamic Law in regulating the Halal Product Industry and how positive Law supports and covers Islamic Law so that it can support the consistent and straight growth of the Halal Product Industry. The type of research used in this study is library research with a qualitative approach, namely research whose object of study uses library data in the form of books as a data source. This research was conducted by reading, studying and analyzing various existing literature, in the form of books, journals, news and research results. Of course, the references that are the main references in this research are all references related to the legal basis of syar'i, the positive legal basis of the halal industry in Indonesia. The conclusion shows that the Islamic Ummah has a position as a mediating group (ummatan wasathan), neither too right nor too left, fair and balanced according to the word of Allah SWT., in QS. Al-Baqarah: 143. Therefore, Allah SWT., that the Muslim Ummah is the best people born for humans, according to what Allah SWT said, in QS. Ali Imran: 110. There are two aspects that can be reviewed regarding the Halal and Haram Halal Product Industry in Indonesia, namely in terms of the concept of Islamic law and the basis of positive law. All aspects that underlie the Halal Product Industry in Indonesia must comply with Islamic law and be protected by legislation.